Parameters Estimation of Lindely Distribution a Comparative Study - Khawlah N. Mahdi, Mohammed Taha Ahmed, Amer Fadel Tawifiq (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study the three-parameter Lindley distribution (LD) and its mathematical and statistical properties such as the moment generating function, quantile function, reliability function and others. And we estimate the parameters of this distribution by simulation study in eight methods; the maximum Likelihood (ML), ordinary least squares (OLS), method of weighted least squares (WLS), percentiles method (P.C), method of maximizing distance multiplication (MDM), Anderson's Darling (AD), Anderson from the right (RAD) and Cramer-von Mess (C-VM) method. According to the simulation study for three types of samples, the maximum likelihood method was the best method, followed closed the Anderson Darling method, then the method of maximizing the multiplication of distances, we use the statistical criteria (BIAS, MSE, MRE), for comparison between the methods.